Total soluble iron in the soil solution of physically, chemically and biologically different soils - Ammari, Tarek Ghassan; Justus Liebig University Giessen (My University, 2005)
Until now not much about Fe concentrations in soil solutions is known because of difficulties to extract the soil solution and to determine the low Fe concentration in these solutions. Therefore a technique was elaborated by which a mixture of 1:1 soil/quartz sand sample with a soil moisture of 80% of maximum water holding capacity was spread in a Buchner funnel and after an incubation time of 3 days extracted under vacuum (-50 kPa). The Fe(III) in solution was reduced by hydroxylamine hydrochloride to Fe2+ and bound to ferrozine both reacting to form a colored complex with a maximum absorption at 562 nm. The reliability of the method was tested by adding a solution with known Fe concentration to extracted samples and by mixing samples with known Fe concentrations. These tests proved a high reproducibility. Further it was found that soil samples analyzed at different dates, i.e., several weeks after the first analysis, yielded the same results. By this technique 32 soils differing much in texture and pH were analyzed. The Fe concentrations found differed in a range from few my little M Fe to about 200 my little M Fe. These concentrations were not related to any soil characteristics. Interestingly, however, was that the calcareous soils had relatively high Fe concentrations. All concentrations found were high enough to meet the plants demand. The high Fe concentrations found in the calcareous soils prove that the Fe chlorosis of plants on such soils is not a question of the Fe availability in soils. Fifty to 90% of the Fe found in the solutions was complexed by organic molecules (i.e., siderophores). The percentage of organic Fe complexes was correlated with the soil pH (r=0.93). The relative Fe buffer power in the soil solution differed much and was not related to any soil characteristics. In the discussion it is argued that the Fe concentrations found in the soil/quartz sand mixture mirror the actual Fe concentration in the soil solution at 80% of maximum water holding capacity. From the results it is concluded that rather soil organic matter and its turnover than inorganic Fe relationships in soils are decisive for the bioavailability of Fe in soils. This is in line with another results obtained by us showing that the Fe concentrations in soil solution depend much on the microbial activity in soils. Stimulating soil microbial activity by adding carbon substrates to the soil microorganisms resulted in higher Fe concentrations in the soil solutions of almost all the tested soils regardless of their extremely different soil properties.
Vollständig lösliches Eisen in der Bodenlösung von physikalisch, chemisch und biologisch unterschiedlicher Böden
Keywords: ddc:570